2010
DOI: 10.1016/j.neuroimage.2010.05.014
|View full text |Cite
|
Sign up to set email alerts
|

BOLD fMRI of visual and somatosensory–motor stimulations in baboons

Abstract: Baboon, with its large brain size and extensive cortical folding compared to other non-human primates, serves as a good model for neuroscience research. This study reports the implementation of a baboon model for blood oxygenation level-dependent (BOLD) fMRI studies (1.5 × 1.5 × 4 mm resolution) on a clinical 3 T-MRI scanner. BOLD fMRI responses to hypercapnic (5% CO 2 ) challenge, 10 Hz flicker visual, and vibrotactile somatosensory-motor stimulations were investigated in baboons anesthetized sequentially wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 74 publications
(89 reference statements)
0
24
0
Order By: Relevance
“…Conversely, the networks of vision, motor or auditory sensitivity described in the resting state persisted regardless of the depth or type of general anaesthesia (Hutchison et al 2010), and no difference between anaesthetics was found after visual stimulation in dogs (Willis et al 2001). Several MRI paradigms in anaesthetized animals have been developed to map brain activation induced by serotonin infusion in the baboon (Wey et al 2010) and cat (Henderson et al 2002) or brain connectivity in the rat (Pawela et al 2009, Zhao et al 2008). …”
Section: Pratical Issues Anaesthesia and Immobilization Of Animalsmentioning
confidence: 99%
“…Conversely, the networks of vision, motor or auditory sensitivity described in the resting state persisted regardless of the depth or type of general anaesthesia (Hutchison et al 2010), and no difference between anaesthetics was found after visual stimulation in dogs (Willis et al 2001). Several MRI paradigms in anaesthetized animals have been developed to map brain activation induced by serotonin infusion in the baboon (Wey et al 2010) and cat (Henderson et al 2002) or brain connectivity in the rat (Pawela et al 2009, Zhao et al 2008). …”
Section: Pratical Issues Anaesthesia and Immobilization Of Animalsmentioning
confidence: 99%
“…Thus, we cannot exclude the possibility that the anesthetic used in the present study could have masked additional between-genotype differences because of NMDAR inhibition by Ketamine. Nevertheless, we believe that the observed genotype differences are valid because high-amplitude cerebrovascular responses were observed under Ketamine/Xylazine anesthesia (Wey et al, 2010;Kim and Jeong, 2013), and the overall magnitude of hemodynamic responses reported here (3-4% change) was similar to previous studies performed with alpha-chloralose (Dubeau et al, 2011). More importantly, the application of NMDAR and AMPAR antagonists blocks the hemodynamic response to somatosensory stimulation under Ketamine/Xylazine anesthesia (Scott and Murphy, 2012), which supports that glutamatergic transmission is preserved under such anesthetic conditions and that our findings of altered cerebrovascular parameters in Nlgn1 KO mice could be linked to modifications in glutamate receptor functions.…”
Section: Discussionmentioning
confidence: 80%
“…The common choices of anesthesia are sevoflurane, isoflurane, ketamine, and propofol. The choice of anesthetics and dosages vary depending on the types of MRI experiments (i.e., anatomical MRI versus functional MRI (fMRI)) and the duration of the MRI exams [4]. It is necessary to monitor the physiological status of anesthetized NHPs during MRI experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Human scanners are however more widely used for imaging large NHPs (macaque and larger species) [4, 79]. The large scanner size and the ease of use for many commonly available MRI protocols make human MRI systems more facile than small-animal imaging systems for translational aspects of NHP imaging research.…”
Section: Introductionmentioning
confidence: 99%